Effect of Deposition Conditions on Stability of PB Films at PEMFC's Operating Temperatures and pH. Issue 6 (1st January 2016) - Khorami, H. Akbari; Jacobs, N.; Wagner, P.; Dyck, A.; Wild, P.; Brolo, A. G.; Djilali, N.
Abstract : Optrodes based on Prussian blue (PB) are promising for hydrogen peroxide detection within PEMFCs to study the Membrane-Electrode-Assembly degradation. The PB film is however required to sustain the harsh environment of PEMFCs. In this work, PB films were deposited through different conditions and soaked in Phosphate-Buffer-Solutions with pH 2 at elevated temperatures for a day. These PB films were characterized using FTIR to analyze their stability following PBS processing at operating temperature and pH corresponding to an operating PEMFC. The PB film prepared using the single-source-precursor at the temperature of 60°C is found to be the most stable.